Kajian Komunikasi Publik Dalam Rangka Menigkatkan Layanan Administrasi Kependudukan Dengan Media Anjungan Dukcapil Mandiri Di Kota Madiun - Ashila, 'Alya Yusfani; Prabawati, Indah (Universitas Negeri Surabaya, 2024)
Public communication aims to build community participation in improving population administration services. Madiun City Dukcapil has an innovation in the field of population administration, namely the Independent Dukcapil Platform. Anjungan Dukcapil Mandiri Madiun City is located in the city center which is crowded with visitors. Although it is located in the city center, many people do not know the existence of the machine. This research is formed from the concept of four variables that play an important role in achieving successful implementation by George C. Edward III, namely communication, resources, disposition or attitude, and bureaucratic structure. A qualitative approach with discourse and content analysis techniques is the method in this research. The result of this research is that Dukcapil Madiun City has not conducted public communication optimally due to uneven socialization. The resource variable also found a slow response from the call center admin. Another finding is that the Anjungan Dukcapil Mandiri machine is often erroneous when used. In this study, recommendations that can be conveyed in improving this service, namely making socialization standards for the village, conducting periodic checks on the machine, and using automatic messages for the call center.